2017
DOI: 10.1080/20008198.2017.1386988
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DSM-5 and proposed ICD-11 criteria for PTSD with DSM-IV and ICD-10: changes in PTSD prevalence in military personnel

Abstract: Background: Recently, changes have been introduced to the diagnostic criteria for posttraumatic stress disorder (PTSD) according to the Diagnostic and Statistical Manual of Mental Disorders (DSM) and the International Classification of Diseases (ICD). Objectives:This study investigated the effect of the diagnostic changes made from DSM-IV to DSM-5 and from ICD-10 to the proposed ICD-11. The concordance of provisional PTSD prevalence between the diagnostic criteria was examined in a convenience sample of 100 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 35 publications
3
22
0
1
Order By: Relevance
“…At least one study of children has also found a superior fit for ICD-11(LaGreca, Danzi, & Chan, 2017). Different answers have emerged regarding prevalence rates with some finding little differences in overall prevalence rates (Hansen et al, 2017;Kuester et al, 2017) and others indicating that ICD is associated with lower rates of disorder (Stammel, Abbing, Heeke, & Knaevelsrud, 2015). Clear answers to both the fit of the data and the prevalence rates associated with ICD and DSM disorders require the use of reliable measures, which have been established.…”
Section: Diagnosis Of Ptsd and Complex Ptsdmentioning
confidence: 99%
“…At least one study of children has also found a superior fit for ICD-11(LaGreca, Danzi, & Chan, 2017). Different answers have emerged regarding prevalence rates with some finding little differences in overall prevalence rates (Hansen et al, 2017;Kuester et al, 2017) and others indicating that ICD is associated with lower rates of disorder (Stammel, Abbing, Heeke, & Knaevelsrud, 2015). Clear answers to both the fit of the data and the prevalence rates associated with ICD and DSM disorders require the use of reliable measures, which have been established.…”
Section: Diagnosis Of Ptsd and Complex Ptsdmentioning
confidence: 99%
“…Our study indicated that the agreement between DSM-5 and ICD-11 was substantial. The ICD-11, which includes only six symptoms compared with DSM-5 (20 symptoms), might benefit due to having fewer items (Brewin, 2005;Kuester et al, 2017). The agreement of 0.79 for Cohen's kappa, suggests an overlap of PTSD diagnoses according to DSM-5 versus ICD-11 although they are not identical.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have directly compared the four sets of diagnostic criteria used in recent years (i.e. DSM-IV, DSM-5, ICD-10, and ICD-11) (Kuester et al, 2017;O'Donnell et al, 2014;Stein et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…shows that his disease is manifested in psychological disadaptation (mental dysfunction) and accompanied by the variety of intra- and interpersonal conflicts, loss of meaning in life or its reinterpretation, collapse of the former ideals and loss of faith in a successful future, in other words, it is a kind of existential crisis. 15 The heavier the trauma, the more likely the disorder is to develop, however, it does not occur in all people, no matter how serious the trauma is. Thus, there are a number of factors that determine a person's vulnerability and ability to recover quickly.…”
Section: Clinical Signs Of the Stress Disordersmentioning
confidence: 99%
“…The picture of mental manifestations of coronavirus syndrome can be divided into several stages, by analogy with reactions to other types of stressful events. 15-17 ,31, 37 …”
Section: Anticipated Symptoms Of Coronavirus Syndromementioning
confidence: 99%